TNFα in MS and Its Animal Models: Implications for Chronic Pain in the Disease - Maguire, Aislinn D.; Bethea, John R.; Kerr, Bradley J. (Frontiers in Neurology, 2021)
Multiple Sclerosis (MS) is a debilitating autoimmune disease often accompanied by severe chronic pain. The most common type of pain in MS, called neuropathic pain, arises from disease processes affecting the peripheral and central nervous systems. It is incredibly difficult to study these processes in patients, so animal models such as experimental autoimmune encephalomyelitis (EAE) mice are used to dissect the complex mechanisms of neuropathic pain in MS. The pleiotropic cytokine tumour necrosis factor  (TNF) is a critical factor mediating neuropathic pain identified by these animal studies. The TNF signaling pathway is complex, and can lead to cell death, inflammation, or survival. In complex diseases such as MS, signaling through the TNFR1 receptor tends to be pro-inflammation and death, whereas signaling through the TNFR2 receptor is pro-homeostatic. However, most TNF-targeted therapies indiscriminately block both arms of the pathway, and thus are not therapeutic in MS. This review explores pain in MS, inflammatory TNF signaling, the link between the two, and how it could be exploited to develop more effective TNF-targeting pain therapies.